2003
DOI: 10.1046/j.0303-6979.2003.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between clinical parameters and cytokine profiles in inflamed gingival tissue and serum samples from patients with chronic periodontitis

Abstract: These results indicate that high variability of cytokine concentrations and low frequency of their detection in serum samples from periodontitis patients make these determinations useless for the detection of disease presence and/or its severity. In contrast, high absolute levels of IL-1beta, TNF-alpha, IL-2 and IFN-gamma and, especially their high ratios to IL-4 and IL-10 found in inflamed tissue biopsies, were closely associated with periodontal disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
281
8
22

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(336 citation statements)
references
References 22 publications
25
281
8
22
Order By: Relevance
“…Our study demonstrated in patients with type 2 diabetes mellitus and chronic periodontitis high levels of cytokines of both, Th1 proinflammatory cytokines, represented by IL-17 and IFN-γ, and Th2 anti-inflammatory cytokines, which consisted of IL-4 and IL-10. Górska et al 22 reported that cytokines play a crucial role in immune and inflammatory responses and the balance between them can determine the outcome of periodontal infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study demonstrated in patients with type 2 diabetes mellitus and chronic periodontitis high levels of cytokines of both, Th1 proinflammatory cytokines, represented by IL-17 and IFN-γ, and Th2 anti-inflammatory cytokines, which consisted of IL-4 and IL-10. Górska et al 22 reported that cytokines play a crucial role in immune and inflammatory responses and the balance between them can determine the outcome of periodontal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic periodontitis sites have shown increased levels of IL-17 in comparison with healthy periodontal tissues [18][19][20][21][22][23] and periodontal pathogens can stimulate the production of IL-17 from T-cells 19 . In this study, the concentration of the cytokine IL-17 was higher in patients with poorly controlled diabetes, confirming the Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Las citoquinas son polipéptidos reguladores que intervienen en la comunicación intercelular con un amplio espectro de propiedades inflamatorias, hematopoyéticas, metabólicas e inmunomoduladoras. Junto con sus receptores asociados forman una compleja red funcional de estricto control biológico, que incluye el feedback o retroalimentación 2,3 . Actúan regulando las células endoteliales y las moléculas de adhesión leucocitarias, hecho imprescindible para que los leucocitos abandonen los vasos sanguíneos y se infiltren en los tejidos circundantes.…”
Section: Resumen Resumen Resumen Resumenunclassified
“…However, the individual's immune response to bacterial insult is responsible for the development or cessation of the disease, including a profile of the immune response regulated by different cytokines (3). Increased levels of immunoregulatory molecules, such as IL-1-b (interleukin-1 beta), IL-6 (interleukin-6), TNF (tumor necrosis factor) and PGE2 (prostaglandin E2), have been observed in periodontitis and periimplantitis sites compared with healthy sites (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%